Computer-Assisted Three-Dimensional Planning for Orbital Decompression. Issue 3 (September 2015) - Mahoney, Nicholas; Grant, Michael P.; Susarla, SrinivasMurthy; Merbs, Shannath
Thyroid-associated orbitopathy is the most common cause of unilateral or bilateral proptosis in adults. A mainstay of surgical treatment is orbital decompression utilizing osteotomies to increase the size of the affected bony orbit to accommodate the larger soft tissue volume. Over the past several decades, numerous approaches have been described for orbital decompression. However, given the intricate osseous and soft tissue anatomy within the orbit, orbital decompression is a potentially hazardous intervention. With advances in three-dimensional imaging and virtual planning, extensive orbital decompressions can be performed safely and efficiently. In this report, we describe two cases of three-wall orbital decompressions using three-dimensional planning.